Unification of economic systems in the global economy: Barriers and preconditions - Svetlana G. Vokina; Yulia S. Zima; Nikolai G. Sinyavsky; Vadim Meshkov; Aleksandra V. Sultanova (Contemporary Economics, 2016)
The purpose of the article is to determine barriers and preconditions for reducing the differences in the level of development in the global economy's countries and to develop recommendations for solving the problem of the global economy's economic systems unification. In order to determine the gap between developed and developing countries, the authors use the comparative analysis method. In order to determine possibilities, problems, perspectives, and threats to overcoming the gap by developing countries, the authors use the SWOT-analysis method. For studying the global economy's economic development disproportions, this research uses specially developed proprietary analysis of gap depth in economic development. As a result of the analysis, the authors determined that the level of economic development of the most developed countries exceeds the level of developing countries by more than four times. This reflects a huge gap depth and a high level of differentiation for countries in the global economy. The authors conclude that barriers of unification of economic systems in the global economy are primarily related to socio-political factors. Preconditions to reducing the difference in level of economic development for countries in the global economy are predetermined by the influence of globalization and international integration of economic systems.
Keywords: F63; 330; Problem of Unification; Economic System; Global Economy; Economic Development Disproportions